ANALISIS PERSEPSI PENDENGAR TERHADAP PENGGUNAAN MAJADALAM LIRIK LAGU GALA BUNGA MATAHARI KARYA SAL PRIADI - Alya Dwi Ningsih; Desti Dean Panggabean; Alisya Sabrina Irawan; Kanita Sari Matondang; Mauliza Az Zahra; Ramadheni Tanjung; Skaryati; Rivay Nuansa Putra Rajagukguk; Clara Deyagatha Br Ginting; Ita Khairani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This quantitative descriptive study aims to describe how listeners perceive figurative language in the song “Gala Bunga Matahari" by Sal Priadi. Data were collected using a 4-point Likert scale questionnaire administered to 70 respondents through purposive sampling. The results showed that most listeners (91.4%) paid more attention to the meaning of the lyrics than the musical elements. The use of the metaphor "Bunga Matahari" (92.9%) and the phrase "Tubungmu tidak merasa sakit lagi" (95.8%) were effective in creating a powerful symbol of loss, comforting, and encouraging emotional acceptance. This way of writing the lyrics effectively enhances emotional communication, triggers visual imagination, and serves as a way for deep personal reflection on loss.